Energy-Based Seismic Risk Evaluation of Tall Reinforced Concrete Building in Vancouver, BC, Canada, under Mw9 Megathrust Subduction Earthquakes and Aftershocks - Tesfamariam, Solomon; Goda, Katsuichiro (Frontiers in Built Environment, 2017)
This paper presents a seismic performance evaluation framework for reinforced concrete (RC) buildings, comprising of shear-walls and gravity frames. The evaluation is undertaken within a performance-based earthquake engineering framework by considering regional seismicity and site-specific ground motion selection. Different engineering demand parameters (EDPs), i.e. maximum inter-story drift ratio and energy-based damage index, are considered as performance indicators. Various prediction models of EDPs are developed by considering four ground motion intensity measures (IMs), i.e. spectral acceleration at the fundamental period, Arias intensity, cumulative absolute velocity, and significant duration of ground motion. For this study, a 15-story RC building, located in Vancouver, British Colombia, Canada, is considered as a case study. Using 50 mainshock and 50 mainshock-aftershock earthquake records (two horizontal components per record and bi-directional loading), nonlinear dynamic analyses are performed. Subsequently, the calculated maximum inter-story drift ratios and damage indices are correlated with suitable IMs using cloud analysis, and the most efficient IM-EDP prediction models are selected by comparing standard deviations of the regression errors. The maximum inter-story drift ratio of the shear-walls is less than 1% for the mainshock and mainshock-aftershock records. The energy-based damage index shows sensitivity to delineate impact of earthquake types and aftershocks. The cumulative absolute velocity is showed to be the most efficient IM for the energy-based damage index.